Induction of Dimorphism in the Basidiomycete Lenzites saepiaria - Scheld, H. W. (1970)
Sugars can serve as the germinant for basidiospores of the wood-rotting fungus Lenzites saepiaria. Hexoses sterilized by autoclaving were better germinants than hexoses that were sterilized by filtration. The degradation products in heated hexose which were responsible for the stimulation of germination were levulinic and formic acid. Another product of hexose degradation, hydroxymethyl furfural, had a marked effect on outgrowth of L. saepiaria basidiospores and on the development of mycelia. Basidiospores that germinated in the presence of hydroxymethyl furfural yielded large rounded bodies that, in some cases, developed as a chain of yeastlike cells. Addition of hydroxymethyl furfural to developing mycelia resulted in the production of chains of round yeastlike structures. Similar results were obtained by treating basidiospores or mycelia with phenethyl alcohol.